Initiatives and Perceptions to Counter Violent Extremism in the Coastal Region of Kenya - Fathima Azmiya Badurdeen; Paul Goldsmith (Journal for Deradicalization, 2018)
The Countering Violent Extremism (CVE) discourse in Kenya reflects the larger Global War on Terror (GWOT) policy framework. Donor-driven governmental approaches support the top-down efforts to counter violent extremism. CVE initiatives now emerging in response to the rise of homegrown violent extremism in Kenya, in contrast, seek to encourage more community participation in the campaign to limit the activities of Al-Shabaab. This article examines existing countering violent extremism (CVE) initiatives in order to elucidate the effectiveness and shortcomings of CVE interventions. The findings are based on an ethnographic study in the coastal region of Kenya comprising of 249 in-depth interviews with key informants, observations and eight focus group discussions. The article maps existing CVE projects across Kenya’s coast including the prevention framework of primary, secondary and tertiary interventions as modelled on preventative public health approaches. Assessment of existing CVE programs provides information elucidating what works and for whom from a community perspective. Feedback from the community is critical for, facilitating effective measures for mitigating the process of youth radicalization in the coast region. The findings reported here recommend periodic consultation with the intended beneficiaries and other CVE initiatives’ stakeholders to enhance the sustainability of the projects.